Does lesion type or severity predict outcome of therapy for horses with equine glandular gastric disease? – A retrospective study. Issue 1 (10th December 2022) - Pratt, S. L.; Bowen, M.; Hallowell, G. H.; Shipman, E.; Bailey, J.; Redpath, A.
Abstract: Background: Equine glandular gastric disease (EGGD) is a common condition of the horse. Misoprostol is reported to be superior to oral omeprazole and sucralfate for treatment. Long‐acting intramuscular injectable omeprazole (LAIOMEP) is a novel treatment shown to be effective in a small population. Objectives: This study aimed to determine LAIOMEP efficacy compared to misoprostol and oral omeprazole and identify characteristics that predict treatment outcome. Methods: All horses that underwent gastroscopy between 2012 and 2019 were reviewed. Lesions were characterised by 4 blinded observers, all of whom are diplomates in equine internal medicine, using established descriptors from the ECEIM consensus statement and subjective severity. Treatment outcome was ranked as worsened, improved or healed. Consensus lesion type, lesion severity and treatment choice were compared to outcome and data screened using univariate analysis (chi‐squared) to determine whether each predicted outcome. Lesion types where univariate analysis predicted a trend ( p <0.2) were included in a multiple‐regression analysis to identify predictors of outcome irrespective of treatment. Results: Only severity significantly predicted final outcome ( p = 0.025) with severe lesions being more likely to improve. Treatment choice did not significantly predict outcome. Overall healing rate was 29% (24 horses), and 43% (44 horses) improved. Treatment healing rates were 23% (10), 12% (7) and 27% (7) for LAIOMEP, misoprostol and oral omeprazole, respectively, with improvement in 69% (14), 76% (21) and 61% (9). 64% of the latter group received sucralfate. Worsening occurred in 7% (6). Treatment length varied with a median of 4 weeks (range 4–20 weeks). Conclusions: This study showed poorer therapy outcome compared to previous studies. The only initial lesion descriptor to predict outcome was severity and treatment choice did not affect outcome. Abstract : When assessing EGGD, only severity predicted final outcome following treatment. Treatment response was also poorer than expected.